Smaller but more frequent dosing of cefepime in the treatment of febrile neutropenia. (June 2022) - Okubo, Lindsay; Andrick, Benjamin; Rampulla, Ricky; Leri, Frederick
Background: Generally national guidelines for febrile neutropenia recommend treatment with cefepime 2 g every 8 h. Due to beta-lactam's time dependent killing effects, it is hypothesized smaller doses given more frequently might be non-inferior. The objective of this study is to retrospectively evaluate the efficacy of cefepime 1 g every 6 h versus 2 g every 8 h in cancer patients with febrile neutropenia. Methods: This retrospective, single-center, cohort study included patients with a diagnosis of febrile neutropenia treated with cefepime during an inpatient encounter. Patients were grouped based on receipt of cefepime 2 g every 8 h (high dose cohort) versus cefepime 1 g every 6 h (low dose cohort). The primary outcome compared the time to defervescence after cefepime initiation between the two dosing strategies. A subgroup analysis of the primary endpoint was conducted in patients who received both cefepime and vancomycin. Results: Ninety-seven patients were included in the high dose cohort, and seventy-six patients were included in the low dose cohort. Baseline characteristics were similar between cohorts with the exception of race. The time to defervescence between the high dose cohort and low dose cohort were comparable between groups (49.2 vs. 46.7 h). The time to defervescence in subgroup analysis of patients who received empiric vancomycin and cefepime was 65.7 versus 59.7. Conclusion: Patients who received cefepime 1 g every 6 h were found to have similar trends in achieving time to defervescence compared to 2 g every 8 h.